Cointegrated Index Mover Stock and Composite Stock Index at ISE (Random Walk Analysis) - Sulastri Sulastri (Program Studi Magister Manajemen FE Unsri, 2009)
Many models of market balance has created by some researchers, one of this is CAPM Model, as the model to measure the market efficiency. The utilization of this model also enables to explain the role of information from public and private and valuable to advantage strategy in investation decision. In CAPM the use of index number as proxy of market information is an important issue. The index number also became a problem if they are not reflected all the market information, because the imbalance of the liquidity of stocks in the market.This research tries to test weather there is or not the cointegration under Index Mover Stock and the Composite Stock Index in ISE. If the IMS only consist of the small number of conyegration stock in CSI, it’s indicate the market information stil not reflected the whole information the public information, and the movement of the public information is influence by the private information, as vice versa.The results indicate the significant cointegration between IMS and CSI, means market information as public still not reflected the the whole available information. It is indicate JSE market still in the Weak Form Efficient Market. This research implicate it is need to be aware in the use of market index in testing the CAPM model (beta score) as proxy as the performance measurement or expected return prediction of individual stock in JSE in Weak Form Efficient Market condition is against the CAPM assumption itself.Keywords: Cointegrated, Composite Index.